Clinical and molecular outcomes from the 5-Year natural history study of SSADH deficiency, a model metabolic neurodevelopmental disorder - Tokatly Latzer, Itay; Roullet, Jean-Baptiste; Afshar-Saber, Wardiya; Lee, Henry H. C.; Bertoldi, Mariarita; McGinty, Gabrielle E.; DiBacco, Melissa L.; Arning, Erland; Tsuboyama, Melissa; Rotenberg, Alexander; Opladen, Thomas; Jeltsch, Kathrin; et al. (Journal of neurodevelopmental disorders, 2024)
Succinic semialdehyde dehydrogenase deficiency (SSADHD) represents a model neurometabolic disease at the fulcrum of translational research within the Boston Children’s Hospital Intellectual and Developmental Disabilities Research Centers (IDDRC), including the NIH-sponsored natural history study of clinical, neurophysiological, neuroimaging, and molecular markers, patient-derived induced pluripotent stem cells (iPSC) characterization, and development of a murine model for tightly regulated, cell-specific gene therapy.